Role of clinical evaluation in the identification of coronary obstructive disorders in patients with stable coronary artery disease. Part I - A. N. Sumin (Российский кардиологический журнал)
To make a decision on choice the type of myocardial revascularization in patients with coronary artery disease (CAD), an invasive coronary angiography (CAG) is necessary. However, in clinical practice, a significant number of patients during CAG fails to detect coronary obstructive disorders, there is the so-called problem of “clean” coronary arteries. Indeed, in the Russian Federation in approximately 50% of cases, CAG does not end with myocardial revascularization, and in patients with suspected CAD, non-obstructive coronary artery lesions are detected in 67% of cases. In the first part of the review, a critical analysis of the clinical evaluation of patients in the selection of patients for CAG was conducted. First stages of the diagnostic process based on clinical evaluation are considered. The review discusses the use for diagnostic purposes more complete set of routine assessment methods and the expanded use of laboratory tests using memetic algorithms.